The complete mitochondrial genome sequence of Eimeria innocua (Eimeriidae, Coccidia, Apicomplexa) - Hafeez, Mian Abdul; Vrba, Vladimir; Barta, John Robert (Mitochondrial DNA. Part A, DNA mapping, sequencing, and analysis, 2016)
The complete mitochondrial genome of Eimeria innocua KR strain (Eimeriidae, Coccidia, Apicomplexa) was sequenced. This coccidium infects turkeys (Meleagris gallopavo), Bobwhite quails (Colinus virginianus), and Grey partridges (Perdix perdix). Genome organization and gene contents were comparable with other Eimeria spp. infecting galliform birds. The circular-mapping mt genome of E. innocua is 6247 bp in length with three protein-coding genes (cox1, cox3, and cytb), 19 gene fragments encoding large subunit (LSU) rRNA and 14 gene fragments encoding small subunit (SSU) rRNA. Like other Apicomplexa, no tRNA was encoded. The mitochondrial genome of E. innocua confirms its close phylogenetic affinities to Eimeria dispersa.
Keywords: Coccidian parasite; Animals; genom protozoální; turkey Eimeria; Phylogeny; Genome, Protozoan; RNA, Ribosomal; RNA ribozomální; Eimeria; Galliformes; fragmented rRNA; zvířata; fylogeneze; Genome, Mitochondrial; genom mitochondriální; mitochondrial genome